Attitudes and perspectives of frontline workers in environmental policy: a case study of Ohio's Environmental Protection Agency and Wisconsin's Department of Natural Resources. Issue 1 (24th October 2012) - Rinfret, Sara R.; Pautz, Michelle C.
<x xml:space="preserve">Abstract</x> This research is an effort to focus on frontline regulators with the Ohio Environmental Protection Agency and Wisconsin Department of Natural Resources. An online survey was conducted of frontline regulators in these agencies to explore their knowledge, attitudes, and perspectives on policy implementation. More specifically, we endeavor to answer how frontline workers implement environmental policy. To analyze these data, we use two categorizations of factors (knowledge and attitudes, and contextual factors) offered by May and Winter (2009) to examine what influences the decision making of frontline regulators in their regulatory interactions. We find that despite common presumptions of adversarialism in the environmental regulatory arena, the frontline environmental inspectors in these states generally have positive attitudes of their regulatory colleagues and cope well with external contextual factors. While our findings are exploratory and descriptive, we argue that they are important for the next generation of environmental policy in the USA. Copyright © 2012 John Wiley & Sons, Ltd.